Gamma-ray spectral variability of HBL 1ES 1959+650 during MJD 57400–58000 and its consequence on leptonic blazar emission model. Issue 4 (16th November 2022) - Ghosal, B; Tolamatti, A; Bhattacharyya, S; Bhatt, N; Yadav, K K; Chandra, P; Das, M P; Tickoo, A K; Rannot, R C; Gaur, K K; Goyal, A; Kumar, N; et al.
ABSTRACT: 1ES 1959+650, a high-energy peaked BL Lac object (HBL) with redshift z = 0.047, is known to exhibit flux and spectral variability in different energy bands. In this work, we primarily considered the simultaneous Fermi -LAT and Swift -XRT data of 1ES 1959+650 to study the flux and spectral variability in the energy ranges (0.1–300 GeV) and (0.6–10 keV), respectively. Using the Fermi -LAT light curve, a stretch of quiescent state and three high flux states of the source were identified. The flux and the spectral variability were studied using flare profiles and flux-index loops. In the γ-ray energies, 1ES 1959+650 clearly showed the evolution 'softer-when-brighter' whereas in the X-rays it showed the trend 'harder-when-brighter'. 1ES 1959+650 also showed quick changes in spectral shape in the γ-ray band when the γ-ray flux was changing during the flares. The spectral energy distributions (SEDs) of the source were constructed using simultaneous data from Fermi -LAT, Swift -XRT, Swift -UVOT during its evolution. The TeV data from TACTIC imaging telescope were also used to construct the SED in the quiescent state. The spectral modelling of the SEDs revealed that due to the spectral variability of 1ES 1959+650, the standard leptonic one zone model cannot be used to explain the emission from this source. Instead a two zone leptonic model is needed to explain the observed SEDs from this blazar.